Desempeño Laboral en el Gobierno Autónomo Descentralizado Parroquial de San Juan - Barrios Chicaiza, Ariana Mercedes (2019)
The present investigation is destined to study the labor performance that the members of the organization have, and the causes that affect in an inadequate organizational environment, in addition it is analyzed how this situation affects the fulfillment of the organizational objectives of the Parish Autonomous Decentralized Government of San Juan, among the factors to be considered in the research, is the job satisfaction of the members of the institution, a fundamental component for an adequate institutional development.